Construction of a mouse model that can be used for tissue-specific EV screening and tracing in vivo - Li, Weili; Wang, Jin; Yin, Xiaojiao; Shi, Huanhuan; Sun, Benben; Ji, Mengru; Song, Huichen; Liu, Jiachen; Dou, Yihao; Xu, Chenghong; Jiang, Xiaohong; Li, Jing; et al. (Frontiers in Cell and Developmental Biology, 2022)
Extracellular vesicles (EVs) play an important role in the communication between tissues and cells. However, it is difficult to screen for and trace EVs secreted by specific tissues in vivo, which affects the functional study of EVs in certain tissues under pathophysiological conditions. In this study, a cre-dependent CD63flag-EGFP co-expressed with mCherry protein system expressing mice was constructed, which can be used for the secretion, movement, and sorting of EVs from specific tissues in vivo. This mouse model is an ideal research tool for studying the secretion amount, target tissue, and functional molecule screening of EVs in specific tissues under different pathophysiological conditions. Moreover, it provides a new research method to clarify the mechanism of secreted EVs in the pathogenesis of the disease.